Agriculture to go hi-tech - Loh , Foon Fong (2012)
SERDANG: There are plans to make farming go hi-tech with information and communications technology (ICT) to attract the young to agriculture, said Agriculture and Agro-based Industries Minister Datuk Seri Noh Omar.